Validity and Reliability Tests on the Nomophobia Instrument with the Rasch Model - Fuady, Ikhsan; Priyansyah, Rifki Nur; Ernawati, Erna; Prasanti, Ditha (Indigenous, 2022)
Abstract. Nomophobia (the fear of being disconnected from a smartphone) severely impacts social and mental problems in society, so it is essential to measure the nomophobia levels to anticipate more severe problems in society. Even so, the validated nomophobia instrument still needs to be looked at to see how it can be used in the current situation. This study, therefore, aims to assess and develop a valid and reliable nomophobia instrument. This research method used a survey approach conducted on 75 students in West Java. Data analysis to test validity and reliability employed Rasch modeling with Winstep, consisting of 1) item and person reliability validity testing, 2) Wright Map person and item instruments, 3) rating scale analysis, and 4) exploratory analysis factors. Then, to find out the level of nomophobia among college students, descriptive statistical analysis was applied. The analysis results revealed that out of 15 instruments, 11 had the feasibility to be used in measuring the nomophobia construct with four dimensions: 1) the dimension of loss of connectedness, 2) the dimension of giving up convenience, 3) the dimension of inability to communicate, and 4) the dimension of inability to access information. Meanwhile, for instrument answers, the Nomophobia scale score is recommended to be ranked from 1 to 4.Keywords: nomophobia; instrument validity; rasch model.